Uncertainty and bias in electronic tide-gauge records: Evidence from collocated sensors. (September 2018) - Pytharouli, Stella; Chaikalis, Spyros; Stiros, Stathis C.
Highlights: Sea level data from ten locations worldwide were analysed. Analysis was based on raw, uncorrected data from collocated tide-gauge sensors. Tide-gauge errors are more frequent and important than was believed before. Isolated tide-gauges probably influenced by unknown errors. Pressure gauges present higher chances of long-term transient bias. Abstract: Understanding noise and possible bias in tide-gauge sensors is important for determining the mean sea level, its fluctuations and their climatic, geophysical and engineering implications, but not an easy task. In the past, this problem has been examined through comparison of different sensors in the laboratory, or through correlations of neighbouring sensors. In this study we identified and studied 10 cases of harbours with fully collocated sensors. Transient differences were found between collocated records. Pressure gauges were found significantly more sensitive to noise than radar-type sensors, and with higher chances of long-term transient bias. The amplitude of the observed bias is important, of the same order of magnitude with tsunami waves in the open sea and with seismic ground displacements. Only 9% of the sensors analysed were found to satisfy the 1 cm accuracy criterion imposed by the Permanent Service for Mean Sea Level (PSMSL).